Modeling of Nitrogen Dioxide (NO2) Concentration and Analysis of Risk NO₂ Exposure Levels for Vulnerable Groups (Pedestrians, Traders, and Settlement Residents) at Simpang Lima Mandai, Makassar City - Muh. Fikruddin Buraerah; Misda Fauici; Franita Leonard; Hasanuddin Hasanuddin (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: The increase in urban population and the growing number of motor vehicles contribute significantly to air pollution. High emissions of nitrogen dioxide (NO₂) from motor vehicles pose significant risks to health. Objective: This study explored the NO₂ dispersion profile from vehicle activity and its impact on the community in Simpang Lima Mandai, a heavy-traffic area and the location of the highest ambient NO₂ concentration in Makassar. Methods: A field survey and AERMOD Gaussian dispersion modeling were used in this quantitative study. Traffic volume, vehicle type, speed, and segment length were classified as primary data, while emission factors (EMEP/EEA 2019; MOVES) BMKG Makassar's meteorological data were classified as secondary data. A bottom-up emissions inventory was used to calculate NO₂ emission loads, and WHO (2021) and PP No. 22/2021 air quality standards were used to compare model results. Results: The model indicated that the average NO₂ concentrations over 1 h (348.8 µg/m³) and over 24 h (82.49 µg/m³) represented high exposure risk in the Simpang Lima Mandai area. The residents from the nearby settlements were found to be more vulnerable because of their long-term residence in the polluted area, with a weekly exposure of 4,452 µg/m³. Motor vehicles are a significant contributor to NO₂ pollution, according to the study. Conclusion:Motor vehicle NO₂ emissions at Simpang Lima Mandai are higher than WHO standards, and the highest exposure was recorded for neighboring residents at 4,452 µg/m³/week. We recommend evidence-based interventions such as enhanced traffic management, additional green buffers, and periodic NO₂ monitoring to protect these high-exposure communities.